2006
DOI: 10.1111/j.1399-0004.2006.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between endothelial nitric oxide synthase and Alzheimer disease

Abstract: Evidence suggests that vascular and inflammatory factors may be important in the etiology of Alzheimer disease (AD). The Glu/Glu genotype at the Glu298Asp variant of the endothelial nitric oxide synthase (NOS3) gene has been tested for association with AD in several Caucasian and Asian populations, with conflicting results. We tested the Glu298Asp variant for association in African American and Caucasian AD patients, unaffected siblings, and unrelated controls from the MIRAGE Study. To explore whether the inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
2
15
0
1
Order By: Relevance
“…Our findings are consistent with the low relevance of the Glu298Asp variant on Alzheimer's disease [65] and pre-eclampsia [66] in populations of mainly European descent. Likewise, our results support findings of a recent meta-analysis, which suggest not only important publication bias in the NOS3 variants literature but also, when considering large studies only (> 500 cases), an irrelevance of both 4a and À786C variants in the risk of ischaemic heart disease [67].…”
Section: Comparisons With Previous Studiessupporting
confidence: 93%
“…Our findings are consistent with the low relevance of the Glu298Asp variant on Alzheimer's disease [65] and pre-eclampsia [66] in populations of mainly European descent. Likewise, our results support findings of a recent meta-analysis, which suggest not only important publication bias in the NOS3 variants literature but also, when considering large studies only (> 500 cases), an irrelevance of both 4a and À786C variants in the risk of ischaemic heart disease [67].…”
Section: Comparisons With Previous Studiessupporting
confidence: 93%
“…Dahiyat et al (1999) first found a significant association of LOAD and homozygosity for the Glu allele and the Glu/ Glu genotype of NOS3 Glu298Asp polymorphism. The finding was confirmed by subsequent studies (Guidi et al 2005;Ntais and Polycarpou 2005;Akomolafe et al 2006), but others have failed to find a significant association (Singleton et al 2001;Kálmán et al 2003;Monastero et al 2003;Tedde et al 2002;Sánchez-Guerra et al 2001;Kunugi et al 2000;Wang et al 2004).…”
Section: Introductionsupporting
confidence: 52%
“…The Glu allele frequencies of the Glu298Asp polymorphism in the Chinese population in our study (88.0%), in Japanese (93.3%), in African American (84.0%), and Caucasian American and European populations (62-75%) implied the differences in genetic background (Guidi et al 2005;Ntais and Polycarpou 2005;Akomolafe et al 2006;Kálmán et al 2003;Monastero et al 2003;Tedde et al 2002;Sánchez-Guerra et al 2001;Kunugi et al 2000).…”
Section: Discussionmentioning
confidence: 65%
“…In the kidney, nitric oxide dilates renal blood vessels and modulates renin secretion. The polymorphisms of eNOS, particularly G894T (Glu298Asp), have already been associated with hypertension, coronary artery disease and atherosclerosis (13,24). The frequencies of Glu298Asp mutation in both non-diabetic and diabetic end-stage renal disease (ESRD) groups are significantly higher than that in healthy controls according to Nagase et al (25)'s study.…”
Section: Discussionmentioning
confidence: 61%
“…Specific allelic variations in the eNOS gene might either directly affect the properties of the eNOS enzyme activity and ethnic differences can be seen (8,10). G894T polymorphism within exon 7 is mostly associated with coronary artery disease, Alzheimer's disease, essential hypertension and ischemic stroke (13,14). A functional 27-bp variable number of tandem repeats (VNTR) in intron 4 (intron 4b/a) of eNOS gene has been reported (8,15).…”
Section: Introductionmentioning
confidence: 99%